2008
DOI: 10.1074/jbc.m800213200
|View full text |Cite
|
Sign up to set email alerts
|

An Unconventional Form of Actin in Protozoan Hemoflagellate, Leishmania

Abstract: Leishmania actin was cloned, overexpressed in baculovirusinsect cell system, and purified to homogeneity. The purified protein polymerized optimally in the presence of Mg 2؉ and ATP, but differed from conventional actins in its following properties: (i) it did not polymerize in the presence of Mg 2؉ alone, (ii) it polymerized in a restricted range of pH 7.0 -8.5, (iii) its critical concentration for polymerization was found to be 3-4-fold lower than of muscle actin, (iv) it predominantly formed bundles rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 64 publications
2
39
2
Order By: Relevance
“…That actin in trypanosomatids is involved in intracellular vesicular trafficking and flagellar-pocket organization is further supported by an earlier study which showed that loss of actin prevents endocytosis and results in enlargement of the flagellar pocket in the bloodstream form of T. brucei (Garcia-Salcedo et al, 2004). However, it is important to mention here that the Leishmania F-actin by itself displays fast dynamics compared with conventional actins (Kapoor et al, 2008), and therefore some monomeric actin is always available to drive the actin dynamics, although at a reduced pace, even in the absence of any actin-dynamics-regulating protein. It might therefore be visualized that deletion of the Leishmania COF gene has only slowed down, but not abolished, the dynamics of filamentous actin, which has resulted only in the slowing down of the actin-based processes.…”
Section: Journal Of Cell Science 123 (11)mentioning
confidence: 53%
See 2 more Smart Citations
“…That actin in trypanosomatids is involved in intracellular vesicular trafficking and flagellar-pocket organization is further supported by an earlier study which showed that loss of actin prevents endocytosis and results in enlargement of the flagellar pocket in the bloodstream form of T. brucei (Garcia-Salcedo et al, 2004). However, it is important to mention here that the Leishmania F-actin by itself displays fast dynamics compared with conventional actins (Kapoor et al, 2008), and therefore some monomeric actin is always available to drive the actin dynamics, although at a reduced pace, even in the absence of any actin-dynamics-regulating protein. It might therefore be visualized that deletion of the Leishmania COF gene has only slowed down, but not abolished, the dynamics of filamentous actin, which has resulted only in the slowing down of the actin-based processes.…”
Section: Journal Of Cell Science 123 (11)mentioning
confidence: 53%
“…In higher organisms, ADF/cofilin is essential for depolymerization of the actin contractile ring that forms between two daughter cells during cell division (Abe et al, 1996). However, in the case of trypanosomatid parasites, cytokinesis is primarily a microtubule-mediated process, and despite the presence of actin and several actin-binding proteins (Sahasrabuddhe et al, 2004;Nayak et al, 2005;Kapoor et al, 2008;Tammana et al, 2008;Katta et al, 2009), their role in these parasites was largely unknown. Our recent studies (Tammana et al, 2008;Sahasrabuddhe et al, 2009) show that the actin-binding proteins Cof and CRN12 have essential roles in flagellar assembly and microtubule remodeling, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By virtue of these activities, ADF/cofilins play a key role in regulating the actin dynamics and associated functions in eukaryotes (7). Functions of the actin cytoskeleton have been considered important not only in higher eukaryotes but also in several parasites that cause lifethreatening human diseases, such as Plasmodium (5,49), Acanthamoeba (10,23), Trypanosoma (13,21), Leishmania (30,47), and others.…”
mentioning
confidence: 99%
“…We also reported that Leishmania CRN12 associates with filamentous actin in Leishmania promastigotes (Nayak et al, 2005;Kapoor et al, 2008), and is retained in the flagellar pocket region and in a few cells at the distal tip (Nayak et al, 2005). We have now further explored the intracellular distribution of Leishmania CRN12 in both the resting and dividing Leishmania cells.…”
Section: Introductionmentioning
confidence: 99%